2000
DOI: 10.1161/01.cir.101.11.1319
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Myosin Phosphatase by Upregulated Rho-Kinase Plays a Key Role for Coronary Artery Spasm in a Porcine Model With Interleukin-1β

Abstract: These results indicate that Rho-kinase is upregulated at the spastic site and plays a key role in inducing vascular smooth muscle hypercontraction by inhibiting myosin phosphatase through the phosphorylation of MBS in our porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
209
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(219 citation statements)
references
References 44 publications
9
209
0
1
Order By: Relevance
“…Both acetylcholine and 5-HT activate ROCK, and ROCK inhibitors have been demonstrated to attenuate agonist-induced coronary vasospasm [56]. ROCK inhibitors also suppress vasospasms in porcine coronary artery induced by chronic treatment with the proinflammatory mediator, inter-leukin-1β [57,58]. Indeed, elevated ROCK expression and activity are observed in vasospastic segment [58].…”
Section: Rock In Acute Coronary Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both acetylcholine and 5-HT activate ROCK, and ROCK inhibitors have been demonstrated to attenuate agonist-induced coronary vasospasm [56]. ROCK inhibitors also suppress vasospasms in porcine coronary artery induced by chronic treatment with the proinflammatory mediator, inter-leukin-1β [57,58]. Indeed, elevated ROCK expression and activity are observed in vasospastic segment [58].…”
Section: Rock In Acute Coronary Syndromesmentioning
confidence: 99%
“…ROCK inhibitors also suppress vasospasms in porcine coronary artery induced by chronic treatment with the proinflammatory mediator, inter-leukin-1β [57,58]. Indeed, elevated ROCK expression and activity are observed in vasospastic segment [58]. Clinically, intracoronary administration of a ROCK inhibitor is effective in preventing coronary artery spasm and myocardial ischemia in patients with vasospastic and microvascular angina, as well as intractable severe coronary spasm following coronary artery bypass grafting [59][60][61].…”
Section: Rock In Acute Coronary Syndromesmentioning
confidence: 99%
“…12,14,18 Serotonin (0.1, 0.3, and 1.0 mol/L) induced contractions of the isolated coronary rings without endothelium, which rapidly developed and reached a maximum in 5 to 8 minutes. The developed tension was expressed as a percentage of that attained in the last precontraction with 62 mmol/L KCl.…”
Section: Organ Chamber Experimentsmentioning
confidence: 99%
“…We have recently demonstrated that Rho-kinase is functionally upregulated at the inflammatory coronary lesions and plays an important role in the pathogenesis of coronary hyperconstriction in our porcine model with interleukin (IL)-1␤. 12 The IL-1␤-treated coronary segment is characterized by luminal reduction caused by neointimal formation and constrictive remodeling. 13 Thus, our porcine model may be useful in the examination of the molecular mechanism of coronary arteriosclerosis in humans.…”
mentioning
confidence: 99%
“…For example, RhoA activity is higher in aortic smooth muscle cells derived from the strokeprone spontaneously hypertensive rat than from the wild-type rat, although the expression levels of RhoA are not different between mutant and wild-type rats (20). Rho-kinase activity is up-regulated, and phosphorylation levels of MYPT1 are increased in the coronary spastic lesion in a porcine swine model (21). Subarachnoid hemorrhage induces sustained Rhokinase activation in the canine basilar artery and subsequent cerebral vasospasm (22).…”
mentioning
confidence: 98%